The Use of Edge Coloring Concept for Solving The Time Schedule Problem at Senior High School (Case Study at SMAN 9 Bandarlampung) - Rahman Indra Kesuma; . Wamiliana; Machudor Yusman (International Conference on Engineering and Technology Development (ICETD), 2012)
Nowadays, the computer’s technology is growing so fast and affects the human’s life. With computer, people can do something easier, faster, more efficient, and so on. At SMAN Bandarlampung, the time schedule for teaching process is still done manually. One person is in charge of doing and making the time schedule so that all the lessons, time, classrooms, and days are supposed to be fixed and suitable for every teacher. However, this is not easy to be done, because there are some factors also that must be considered, for example: teacher who also put in structural position such as headmaster or vice headmasters. Besides, under Indonesian’s regulations, the teacher whose certificate to educate must teach at least a certain hour per week. Therefore, in order to handle this condition, we design and develop a system so that the problem can be solved easily. We use the concept of edge coloring to match the schedule. The data are divided into three sets: the set of active time, the set of classes and classroom, and the set of  teachers’ obligation (which include : the data of teachers and their subjects/lessons, and how many time/hours needed to teach for every teacher. The system developed is running well and we will be discussed in the paper.